An Investment Framework for Nutrition in Kenya : Reducing Stunting and Other Forms of Child Malnutrition - Eberwein, Julia Dayton (World Bank, Washington, DC, 2017)
This paper builds on global experience and Kenya’s specific context to identify an effective approach to scaling up nutrition and provide an estimate of costs and benefits of key nutrition interventions. It is intended to help guide the selection of the most cost-effective interventions as well as strategies for scaling up a package of interventions tailored to Kenya’s specific needs. The paper considers high-impact nutrition-specific interventions that largely rely on typical health sector delivery mechanisms. The authors estimate that the costs and benefits of implementing 11 critical nutrition-specific interventions will require a yearly public and donor investment of 76 million dollars. The expected benefits will be substantial: annually more than 455,000 disability adjusted life years (DALYs) will be averted, over 5,000 lives saved, and more than almost 700,000 cases of stunting among children under five averted. This investment will be very cost-effective with an estimated cost per DALY averted of 207 dollars cost per life saved of about 18,600 dollars and a cost per case of stunting averted of 135 dollars. Economic productivity can potentially increase by 458 million dollars over the productive lives of beneficiaries. However, the authors also calculate intermediate scale-up scenarios since it may not be feasible for the Government of Kenya or its partners to achieve full coverage in the near term. The authors compare the costs and benefits associated with three different scenarios: first, prioritizing counties, focusing the investment on counties with a high burden of stunting; second, prioritizing interventions, focusing on only a subset of the most effective interventions; and third, prioritizing both counties and interventions, delivering only the most effective subset of interventions to high-burden counties. The authors determined that the third scenario is the most cost-effective and least costly. Scaling up the most cost-effective interventions in 37 high-burden counties will avert almost 295,000 DALYs and save over 3,000 lives per year for an annual public and donor investment of 48 million dollars.